Congenital Nephrotic Syndrome and Peripheral Veno-occlusive Disease Secondary to Congenital Cytomegalovirus Infection: A Case Report - Begum, Nurun Nahar Fatema; Hossain, Muhammad Rabiul; Sarker, Md Ferdousur Rahman; Alam, Jahangir (Journal of Armed Forces Medical College, Bangladesh, 2015)
Abstract not available Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014